Cooperation Instead of Integration. British Struggle with the Treaties of Rome (Economic and Political Thought, 2012)
The subject matter of the article is the analysis of the course of diplomaticstruggle for the institutional shape and character of the process of unitingWestern European countries in the years 1955–1960. It was a special periodin the history of the European integration. That was when the countries ofWestern Europe formally split into two groups having two different ideas ofhow to unite Europe. Creating the EEC and the EFTA was an institutionalmanifestation of that division. The former had some incorporated mechanismsof supranational integration requiring a cession of sovereignty. Thelatter was heading for gradual abolition of trade restrictions and coordinationof sovereign countries’ economic policy. The differences in the interests andstands of particular states that appeared then have not lost their importance until now.The article presents an analysis and interpretation of the European integrationthat differs strongly from the type dominating in science. It is notaimed at characterizing the content and shape of the ready-made product ofthe integration idea like the EEC and the EFTA. It shows the other side ofthe picture, i.e. the course of long-lasting and very strong British diplomaticstruggle for halting the pace and range of supranational integration of WesternEurope and explains the reasons of British failures in the field. It turnsout that, in the British policy regarding the European integration, the factorof continuity prevails over the factor of changes.